Forest bathing activity as a tool to promote wellness tourism in Thailand - Rodtook, Pimonpat; Simpattanawong, Dararat; Ruenbanthoeng, Thongrob; Na Nongkhai, Krittaya (Humanities, Arts and Social Sciences Studies, 2024)
This study broke new ground by exploring forest bathing in Thailand, examining its potential to improve health within the country's unique environment and culture. Recognizing the practice's novelty, the research assessed both feasibility and acceptability, along with its effectiveness in boosting well-being. Bespoke activities designed to optimize the experience for Thailand's diverse landscapes were also developed. Additionally, the study evaluated forest bathing's potential as a novel and attractive wellness tourism option in Thailand, highlighting its health benefits. The study engaged 94 volunteer tourists, randomized based on location and availability, who participated in forest bathing activities across varied ecosystems—National Park, Community Forest, and Urban Forest. A significant outcome was the observable decrease in participants' systolic blood pressure levels after engagement. This decrease, averaging approximately 6.6%, sparked discussions on its clinical relevance compared to other health interventions. To understand forest bathing's effects comprehensively, the study tracked systolic and diastolic blood pressure before and after the activity. It also incorporated psychological measures, including the Perceived Stress Scale (PSS) and a happiness assessment. The latter revealed that the vast majority of participants (88.3%) reported high levels of happiness. This research significantly advances forest bathing as a sustainable health tourism model in Thailand by providing early evidence of its effectiveness across diverse landscapes and reinforcing its adoption. The study highlights the importance of merging physiological and psychological assessments, offering a more comprehensive method to evaluate forest bathing's therapeutic potential, thereby enhancing its feasibility and maximizing its benefits within Thailand's unique environmental contexts.